Paragenetic features of the composition of chromespinelides from Dyukunakh placer (Yakutia) (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: In our study, we investigated the paragenetic features of the composition of chromespinelides from the noncommercial Dyukunakh placer (Yakutia) using the specialized software MineralogicalAnalyse. The ore bodies of diamonds, due to which the placer was formed, have not been identified yet. Therefore, the placer is of exploratory interest. Besides diamonds, the placer also contains garnet and chromespinelide. Methodology: The main function of the MineralogicalAnalyse programme is to determine the paragenesis of kimberlite minerals based on their composition. It is able to recognise the chromespinelides of 20 paragenesis. A total of 457 chromespinelide grains from the deposits of the Dyukunakh placer were studied. The composition of the chromites was preliminarily analysed using an electron microprobe. All the results were then recalculated using MineralogicalAnalyse in order to determine the paragenetic features of the chromespinelides. Results and discussion: The article details the composition of the chromespinelides with paragenesis that can be determined by the programme and described their relationships. The study determined that over 70% of the chromespinelides in the Dyukunakh placer are of non-kimberlite genesis. Kimberlite chromespinelides are of subordinate importance (23.6%). Among the typical kimberlite chromespinelides in the placer sediments varieties from non-diamondiferous lherzolites prevail. Conclusions: Non-kimberlite genesis chromespinelides found in the placer cannot be associated with diamonds and garnets in terms of common ore bodies. Therefore, it would be correct to refer to the association of kimberlite minerals in the Dyukunakh placer not as to pyrope-chromespinelide, but as to pyrope or diamond-pyrope association. Thus, the MineralogicalAnalyse programme provides more reliable data regarding the genesis of chromespinelides not only in kimberlites, but also in placers.
Keywords: kimberlite tracer minerals; paragenesis; diamondiferous; chromespinelides; kimberlites; placer